2021
DOI: 10.1097/rct.0000000000001218
|View full text |Cite
|
Sign up to set email alerts
|

Texture Analysis of Tumor and Peritumoral Tissues Based on 18F-Fluorodeoxyglucose Positron Emission Tomography/Computed Tomography Hybrid Imaging in Patients With Rectal Cancer

Abstract: This study aimed to determine whether texture parameters could be used in differentiation between the tumor and the peritumoral tissues based on hybrid 18 F-Fluorodeoxyglucose positron emission tomography/ computed tomography imaging for patients with rectal cancer.Methods: Seven parameters, including heterogeneity, entropy, energy, skewness, kurtosis, standard deviation, and average brightness, were extracted from positron emission tomography/computed tomography scans of 22 patients (12 male and 10 female; me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 73 publications
(137 reference statements)
0
4
0
Order By: Relevance
“…These studies defined the peritumoral region by drawing along the mesorectal fascia. However, some studies have defined the peritumoral region as the area immediately surrounding the tumor [ 20 , 26 , 35 37 ]. Therefore, it is uncertain whether we should combine intratumoral and MRF radiomics features or intratumoral and peritumoral regions immediately surrounding the tumor.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These studies defined the peritumoral region by drawing along the mesorectal fascia. However, some studies have defined the peritumoral region as the area immediately surrounding the tumor [ 20 , 26 , 35 37 ]. Therefore, it is uncertain whether we should combine intratumoral and MRF radiomics features or intratumoral and peritumoral regions immediately surrounding the tumor.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies showed that the MRI-based radiomics signature score (Radscore) of the primary tumor could be used to identify lymph node metastasis (LNM) and tumor deposits in rectal cancer [ 16 , 17 ]. However, most of these studies only focused on intratumoral regions, while peritumoral regions, which may have important information about the tumor, were excluded [ 18 20 ]. Heterogeneity exists not only in cancer cells but also in nonmalignant cells and infiltrating cells around the tumor, usually referred to as the peritumoral microenvironment [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…Several previous studies in other tumors indicated that peritumoral regions were defined as the area immediately surrounding the tumor ( 18 , 20 , 32 , 33 ). Some studies also reported metabolic changes in the peritumoral region, including increased uptake of FDG by the tissues adjacent to the tumor compared with distant tissues ( 34 , 35 ). Therefore, we chose a 3-mm area around the tumor boundary as the peritumoral region according to previous studies ( 18 , 20 ).…”
Section: Discussionmentioning
confidence: 99%
“…We then calculated the Moran’s spatial autocorrelation index as a quantitative measure of heterogeneity in the intracellular Bax distribution with Autocorrelation v.1.0. (NCI, Kyiv, Ukraine) [ 97 , 98 ].…”
Section: Methodsmentioning
confidence: 99%